Trabalho, família e política: a perspectiva de São Sepé/rs durante a ditadura civil-militar - Pereira, Felipe Rios (2016)
This research aims to discuss the scenery of social, cultural and political disputes and ressignifications ocurred during the years of 1970 to 1973 in São Sepé, Rio Grande do Sul, Brazil. Thereunto, it is considered a scenery of migrations from rural to urban zones, resulting in a process of district growth, mainly marginalized ones, and in the modification of spatiality and realities related to the study subjects. The limitation of time and space is the outcome of a larger time frame study, which seeks to understand the Brazilian Civil-Military Dictatorship from the perspective of a city distant from big capitals and of the impacts resulting in the organization and identification of workers in this context. Therefore, will be discussed the actuations, identifications and ressignifications involving different areas, approaching the changes in structures of family, gender, labor, politics and relations to the basic States services. For that, oral testimonys, editions of local journal A Palavra (1971-1973) and records of the City Counsil (1964-1976) are considered and synthetized, trying to understand and textualize the experiences of that group in regards to both the perspective of the imposed Civil-Military Dictatorship and the modifications in the economic scheme that brought more power to the dominant class, in a micro and macro sphere, which affected these social classes.